SMART CITIES AND URBAN DESIGN: INTEGRATING IOT TECHNOLOGIES IN SUSTAINABLE ARCHITECTURE - Hamidova Mohigul Hayotovna; Vohidov Shakhzod Kenjayevich (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Abstract: This paper explores the integration of smart technologies—particularly the Internet of Things (IoT)—in the design of sustainable urban environments. As global urbanization accelerates, cities are under pressure to balance growth with environmental stewardship and livability. Smart architecture, which merges digital systems with built environments, provides real-time data that supports energy efficiency, security, public services, and environmental control. The research examines global smart city case studies and evaluates how IoT can be adapted into the urban planning strategies of developing nations, including Uzbekistan. The findings emphasize that IoT integration in architecture is no longer a luxury, but a necessity for responsive and resilient city planning.